EXPRESSION OF MRNAS FOR TYROSINASE GENES ON EXPOSURE TO PLANT EXTRACT/COMPOUNDS - Cheung, W. K.; Lall, N.; Mapunya, B.; Naidoo, S.; Houghton, P. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Over production of melanin pigment results in hyperpigmentation disorders. Melanin is produced by melanocyte cells in the basal layer of the dermis. Ineffectiveness of the present depigmenting agent with side effects led to the exploitation of alternative solutions to the problem. Several South African plants were selected to test their activity on tyrosinase. Ethanol extracts were evaluated for their inhibitory effect on tyrosinase and antioxidant activities in vitro, using a colorimetric procedure. Active extracts were investigated for their inhibitory effect on melanogenesis in cultured B16 melanoma cells. IC50 of Sideroxylon inerme, Greyia flanaganii and Galenia africana were found to be 63.12±1.2, 148±0.7 and 240±1.3 ìg/ml respectively when L-tyrosine was used as a substrate. Two active compounds, epigallocatechin gallate and procyanidin B1, isolated from S. inerme, exhibited IC50 values against monophenolase of 30 and >200 ìg/ml respectively. S. inerme exhibited 37% reduction of melanin content at 6.2 ìg/ml in melanocytes without being significantly toxic to the cells. S. inerme, epigallocatechin gallate and procyanidin B1 exhibited antioxidant DPPH radical scavenging activities with EC50 values of 1.54, 1.33 and 1.68 ìg/ml respectively. The inhibition of tyrosinase activity relative to the inhibition of its activity at transcriptional level was evaluated by determining the degree of expression of mRNAs for the tyrosinase gene by the extracts and the purified compounds with semi-quantitative RT-PCR. S.inerme extracts at 25 ìg/ml was evidenced as a potent tyrosinase inhibitor in the mechanism studies. S. inerme showed promising results for skin-depigmentation and clinical trials are underway. Acknowledgements: NRF, Royal Society.